A method for coupled arch dam-foundation-reservoir seismic behaviour analysis. - Camara, R.J (Earthquake engineering & structural dynamics.)
This paper presents a method for coupled arch dam-foundation-reservoir seismic behaviour analysis. The dam is discretized by finite elements (FE) and the foundation and reservoir are discretized by boundary elements (BE). The opening of contraction joints and the spatial variability of the seismic action is taken into account. The study of Pacoima dam by this method is also presented. The computed results show that no cracks were to be expected due to the vibrations induced during the Feb 9, 1971 San Fernando earthquake.